Evaluation of dynamic behaviour of floating single piles embedded in soft clay layer under lateral harmonic and impulse loading - Suhail, Salman Ali; Pham, Huy Giao; Noppadol Phien-Wej; Kunnawee Kanitpong; Suttisak Soralump; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
Pile is a deep foundation that is used to support the load coming from superstructure to the deeper stiff soil or rock strata. Piles are generally adopted as an appropriate foundation type for tall buildings, long span bridges, offshore structures etc. In general, piles are designed for vertical loads only. However, they have to withstand significant loading on account of lateral vibrations such as, those caused by earthquakes, wind or machine vibrations, etc. The design of piles subjected to lateral vibration loading is challenging task as it involves consideration of simultaneously occurring coupled phenomenon. In the past decades, various researchers, had proposed numerical and analytical solutions to investigate dynamic response of piles. Limited number of experimental studies were also performed to authenticate the exactness of numerical methods. The equivalence of experimental response with numerical simulation shows discrepancies in terms of prediction of natural frequency and pile head displacement responses. As a result, fine tuning i.e. adjustment of soil mechanical properties or use of calibration factors, is adopted to enhance the precision of the numerical responses. With an advancement in computation technology, finite element method gains popularity among the researchers. However, studies based on finite element method lacks experimental validation. Also, detailed nonlinear time history analysis of 3D finite element model of soil-pile interaction demands significantly high computational cost. The reduced dimension finite element model (RDFEM) proposed by Thammarak (2009) is a useful tool to illustrate realistic soil-pile interaction with significantly less computational cost. However, the capability of RDFEM to predict dynamic behavior covering full range of resonant responses and lateral pile response is not verified with an experimental results. In this research, a complete framework to investigate dynamic response of single floating piles subjected to harmonic vibration loading is presented. We verified the capability of RDFEM to predict the complete dynamic behavior and lateral pile response by comparing it with full scale experiments. Three piles of different diameters were prepared. Harmonic and free vibration tests were performed in the field to obtain full range of resonance responses of pile-soil systems. Numerical simulations were also performed by conventional Winkler{u2019}s beam on spring foundation (WBSF) model and by 3D closed form solution in frequency domain, as well as in addition to RDFEM. Soil dynamic modulus and Poison{u2019}s ratio were obtained directly from field measurements v by performing seismic cross-hole test. Root mean square error (RMSE), a statistical parameter has been used to investigate mismatching between experiment and numerical responses. The results highlighted that equivalent 3D RDFEM can effectively simulate the full range of resonance responses and lateral pile response with high precision. The 3D closed form solution in frequency domain provides an accurate prediction of natural frequency of floating piles however, slight discrepancies in the pile head displacement responses were observed judging from RMSE values. Much higher discrepancies in natural frequency prediction and pile head displacement responses, were observed by WBSF model due to its obvious limitation of inability to incorporate shear interaction among the soil springs. An interesting observation was noted that the discrepancies in WBSF model reduced with an increase in the diameter of piles. This may be because shear among the soil slices in the large diameter are considerably less than the small diameter slender piles.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Geotechnical and Earth Resources Engineering
Thesis (Ph.D.) - Asian Institute of Technology, 2021
Keywords: Piling (Civil engineering) -- Materials -- Dynamic testing; Geology -- Thailand; Clay -- Thailand